2020
DOI: 10.3389/fphar.2020.00378
|View full text |Cite
|
Sign up to set email alerts
|

Isoliquiritigenin Derivative Regulates miR-374a/BAX Axis to Suppress Triple-Negative Breast Cancer Tumorigenesis and Development

Abstract: Triple-negative breast cancer (TNBC) is a subtype of breast cancer that accounts for the largest proportion of breast cancer-related deaths. Thus, it is imperative to search for novel drug candidates with potent anti-TNBC effects. Recent studies suggest that isoliquiritigenin (ISL) can significantly suppress the growth, migration, and invasion of breast cancer cells. We previously synthesized ISL derivatives and found that 3′,4′,5′,4″tetramethoxychalcone (TMC) inhibits TNBC cell proliferation to a greater degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…The brown module contained 730 genes and the blue module contained 920 genes, of which 104 hub genes (38 genes in brown module and 64 genes in blue module) in above modules were identi ed according to the lter standard (MM 0.6, GS 0.3). Literature search in PubMed suggested that the majority of the hub genes such as UHRF1, HMMR, AXIN1 and BAX, have been involved in the occurrence, progression and distant metastasis of breast cancer [53][54][55][56]. Among those 104 hub genes, we chose four never reported genes in breast cancer, namely CENPL, ISG20L2, MRPL3, and LSM4, to further explore their correlations with clinicopathological variables as well as their diagnostic and prognostic values.…”
Section: Discussionmentioning
confidence: 99%
“…The brown module contained 730 genes and the blue module contained 920 genes, of which 104 hub genes (38 genes in brown module and 64 genes in blue module) in above modules were identi ed according to the lter standard (MM 0.6, GS 0.3). Literature search in PubMed suggested that the majority of the hub genes such as UHRF1, HMMR, AXIN1 and BAX, have been involved in the occurrence, progression and distant metastasis of breast cancer [53][54][55][56]. Among those 104 hub genes, we chose four never reported genes in breast cancer, namely CENPL, ISG20L2, MRPL3, and LSM4, to further explore their correlations with clinicopathological variables as well as their diagnostic and prognostic values.…”
Section: Discussionmentioning
confidence: 99%
“…ISL-derived new compounds offer another solution to improve the bioavailability and water-soluble issues [ 31 , 32 , 33 , 34 , 35 , 36 ]. Considering the chalone structure, the α,β-unsaturated ketone is an important part of its biological activity by modifying on the phenol ring to improve the performance of ISL.…”
Section: Isl’s Metabolites Pharmakinetics and Pharmacological Efmentioning
confidence: 99%
“… 2′,4′-dimethoxy-4-hydroxychalcone ( Figure 2 e): shows in vivo antidiabetic activity [ 35 ]. 3′,4′,5′,4″-tetramethoxychalcone (TMC; Figure 2 f): Introducing methylation of hydroxy groups significant increase cytotoxic activity in breast cancer [ 31 ], especially targeting on triple-negative breast cancer (TNBC) [ 33 ]. ISL-17 ( Figure 2 g): A fluorine atom was introduced to the structure of ISL named ISL-17 showed the anti-tumor activities in gastric cancer [ 32 ].…”
Section: Isl’s Metabolites Pharmakinetics and Pharmacological Efmentioning
confidence: 99%
See 2 more Smart Citations